A double-choking theory as an explanation of the evolution laws of ejector performance with various operational and geometrical parameters. (15th February 2020) - Tang, Yongzhi; Liu, Zhongliang; Li, Yanxia; Yang, Nan; Wan, Yangda; Chua, Kian Jon
Highlights: A double-choking theory is proposed. A quantitative analysis of the entrainment choking flow has achieved. The inherent reason behind the evolution law of ejector performance is illuminated. The fundamental link between entrainment performance and choking flow is revealed. The evolution laws under various operational and geometry parameters have explained. Abstract: There are few systematic studies to investigate the inherent reason behind the evolution law of ejector performance, only some simple qualitative or roundabout analysis. In this paper, a double-choking theory is proposed to provide an in-depth explanation of the evolution laws of ejector performance. The systematic investigation and quantitative analysis focus on the influences of various operational and geometrical parameters on the ejector choking flows. Key results revealed that the flow area of the primary jet flow at the choking cross-section Apy almost linearly increases with higher primary flow pressure pp0, while the entrainment choking area Aey declines instead, and thus the entrainment ratio ε decreases. The mixing pressure py significantly increases with entrainment pressure pe0, and Apy partly reduces. Consequently, Aey becomes larger and ε is accordingly with an over-double increase. Apy undergoes a continuous decrease when the area ratio of primary nozzle λt increases, and thus ε rises consistently although Aey1 eventually experiences a slight decrease. However, the choking state of the entrained flow would discontinue as λt exceeds its critical value λtc . Additionally, Aey increases substantially when the area ratio of the constant-area section λ3 enlarges, while Apy and py always remain unchanged. Accordingly, ε follows the same increasing trajectory as Aey . These impactful results could serve as an essential guide for optimizing the ejector design, and also ensure a clearer perspective to understand the fundamental link between the ejector's entrainment performance and choking flow.